Aortic chemodectoma causing a lymphocyte‐rich effusion in a cat. Issue 4 (18th October 2018) - del Busto, I.; Stiborova, K.; Villiers, E.; Ferreira, A.J.; Bode, E.F.
Abstract : A 13‐year‐old neutered male domestic shorthaired cat presented to a primary care practice with a few days history of dyspnoea. Pleural effusion was diagnosed radiographically. Thoracocentesis was performed and analysis of the effusion was consistent with a lymphocyte‐rich effusion (presumed chylothorax). The cat was referred for further investigations to determine the cause of the effusion. Subsequent CT and echocardiography revealed a heart base mass that was seen to infiltrate the interventricular septum. Fine needle aspiration of the mass was performed. Cytological evaluation revealed it to be neuroendocrine in origin, consistent with a chemodectoma. There was no evidence of metastatic disease. The cat was discharged for palliative care only and survived symptom free for a further six weeks at which time it was euthanased due to recurrence of pleural effusion. To the authors' knowledge this is the first reported case of lymphocyte‐rich effusion due to a chemodectoma in a cat.